Attitudes of physicians and patients toward immediate and intraoperative chemotherapy treatment in colon cancer - Mehraneh D. Jafari; Andrea Mesiti; Julianna Brouwer; Chelsea McKinney; Lari B. Wenzel; Alessio Pigazzi; Jason A. Zell (Cancer Treatment and Research Communications, 2024)
Introduction: We have shown in a Phase I trial that immediate adjuvant chemotherapy (IAC) during surgical resection and immediately postoperative is safe and feasible in patients with colon cancer (CC). IAC avoids delays in adjuvant treatment and has the potential to improve survival and quality of life. We aim to determine patients and providers attitudes toward this novel multidisciplinary treatment approach. Methods: Two web-based surveys were administered to newly diagnosed CC patients, survivors, surgeons and oncologists. Surveys assessed treatment preferences and perceived barriers to IAC. Chi-square tests were conducted to compare differences between patients’ and providers’ responses. Results: Responses were collected from 35 patients and 40 providers. Patients were more willing to: (1) proceed with IAC to finish treatment earlier thus possibly improving quality of life (p = 0.001); (2) proceed with IAC despite potential side effects (p < 0.001); and (3) proceed with a dose of intraoperative chemotherapy even if on final pathology, may not have been needed (p = 0.002). Patients were more likely to indicate no barriers to collaborative care (p = 0.001) while providers were more likely to cite that it is time consuming, thus a barrier to participation (p = 0.001), has scheduling challenges (p = 0.001), and physicians are not available to participate (p = 0.003). Conclusions: We observed a discordance between what providers and patients value in perioperative and adjuvant CC treatment. Patients are willing to accept IAC despite potential side effects and without survival benefit, highlighting the importance of understanding patient preference.